2010
DOI: 10.1152/japplphysiol.00633.2010
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 and CCR2 variants are associated with skeletal muscle strength and change in strength with resistance training

Abstract: Baseline muscle size and muscle adaptation to exercise are traits with high variability across individuals. Recent research has implicated several chemokines and their receptors in the pathogenesis of many conditions that are influenced by inflammatory processes, including muscle damage and repair. One specific chemokine, chemokine (C-C motif) ligand 2 (CCL2), is expressed by macrophages and muscle satellite cells, increases expression dramatically following muscle damage, and increases expression further with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Interestingly, this variant showed sexually dimorphic results: only males had an association in both cohorts, which is consistent with the previous EMD and FAMuSS cohorts (17,19), and additional articles showing the genetic influence on fitness phenotypic traits (24,25). This suggests that the sex-specific genetic architecture influencing phenotypes needs to be incorporated into the design of individualized exercise interventions to optimize results.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Interestingly, this variant showed sexually dimorphic results: only males had an association in both cohorts, which is consistent with the previous EMD and FAMuSS cohorts (17,19), and additional articles showing the genetic influence on fitness phenotypic traits (24,25). This suggests that the sex-specific genetic architecture influencing phenotypes needs to be incorporated into the design of individualized exercise interventions to optimize results.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, we wanted to compare and quantitate the genotype effect on an acute exercise intervention (single bout) versus a long-term 12-week resistance training intervention. Therefore, we included the following two different exercise cohorts: 1) Eccentric Muscle Damage (EMD) cohort allowed us to evaluate the effects of acute resistance exercise to exhaustion (16,17); and 2) the Functional Single Nucleotide Polymorphisms Associated with Muscle Size and Strength Study (FAMuSS) provided evaluation of a chronic resistance exercise program, a longitudinal 12-week resistance exercise training cohort (18,19). In this article, we demonstrated that two copies of the protective allele (TT) against the development of T2D are associated with a positive response to an acute resistance training exercise bout and show an association with pre-exercise measures of skeletal muscle size and strength.…”
Section: Slc30a8 Nonsynonymous Variant Is Associated With Recovery Fomentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, chemokine receptors have an important effect on the mobilization of leucocytes and regulation of inflammatory response after strength exercise (Harmon et al, 2010;Jajtner et al, 2014). Due to the fact that exercise is a physiological stress and has similar immune responses to infections and sepsis (Walsh et al, 2011), we believe the CC chemokine receptor type 5 (CCR5), a protein found on the cell surface of many leucocytes attracted to infected tissues (Thomas, 2004), can be influenced by physical exercise sessions, especially of the strength training variation.…”
Section: Introductionmentioning
confidence: 99%